Don't get addicted to drugs, for future quality of life - Masayu Endang Apriyanti (Politeknik Bina Madani, 2021)
This community service activity aims to provide education about the dangers of drugs to ourselves or one of our family members, because it has negative impact on the quality of life and future. That’s why we should all be aware of drugs. Especially the target is more focused on our children who are not yet strong so impressionable. With this counseling, It is hoped that all of us as parents, government officials from the lowest until highest levels, community leaders and especially teenagers will be able to protect themselves so as not to slip into drugs. If we are not addicts, then the quality of life will be good, because we are healthty, able to focus on activities, carry out each task and role properly, so that we can produce the best works throughout life, which then along with these achievements will certainly affect how to achieve the quality of our future life, both the future in this world and the hereafter. This article was made from the results of the implementation of Abdimas in September 2018 at Perum Bekasi Elok 1, RW 010, Jejalen Jaya, Tambun, Bekasi. The implementation of this community service is expected to have a good impact on adolescents to strengthen their fortress against various sweet seductions of drugs so their future quality of life can be achieved optimally, which can be proven by being able to achieve all the goals maximally.